1986
DOI: 10.1111/j.1526-4610.1986.hed2601009.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin and Migraine: Effect of L‐Dopa on Plasma Prolactin Levels in Migraineurs and Normals

Abstract: SYNOPSIS Since in migraineurs a change in dopaminergic tone has been hypothesized and since in man prolactin secretionby the lactotroph cells is controlled by hypothalamic inhibitory factors (of which dopamine is the best known), wedecided to investigate plasma prolactin (PRL) response to L‐Dopa in a group of migraineurs.We tested 5 women suffering from common migraine and 5 healthy women as controls.A different behaviour of PRL secretion was observed in the two groups. In migraineurs the inhibition of PRLsecr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 8 publications
3
12
1
Order By: Relevance
“…Some authors have suggested hypersensitivity of dopamine receptors based on the observation that migraineurs showed higher PRL after taking dopaminergic agents [6][7][8][9]. Reduced responsiveness of pituitary lactotroph cells to the effect of dopaminergic agents has also been postulated on the basis of a less marked inhibition of PRL secretion to Ldopa in migraine [10]. It is difficult to explain our result, or similar ones reported in the literature, by using this hypothesis.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Some authors have suggested hypersensitivity of dopamine receptors based on the observation that migraineurs showed higher PRL after taking dopaminergic agents [6][7][8][9]. Reduced responsiveness of pituitary lactotroph cells to the effect of dopaminergic agents has also been postulated on the basis of a less marked inhibition of PRL secretion to Ldopa in migraine [10]. It is difficult to explain our result, or similar ones reported in the literature, by using this hypothesis.…”
Section: Discussioncontrasting
confidence: 56%
“…Some authors suggest a hypersensitivity of dopamine receptors based on the observation that migraineurs showed higher PRL after taking dopaminergic agents [6][7][8][9]. Reduced responsiveness of pituitary lactotroph cells to the action of dopaminergic agents has also been postulated [10]. In 1989, Awaki et al [11] actually suggested a serotoninergic hyperfunction rather than a dopaminergic dysfunction.…”
mentioning
confidence: 99%
“…A variety of headache phenotypes has been associated with pituitary tumors [69]. Some authors suggest a hypersensitivity of dopamine receptors, based on the observation that, some headaches showed higher prolactin (PRL) after taking dopaminergic agents [10]. Other authors suggested a serotoninergic hyperfunction rather than dopaminergic dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors suggest a hypersensitivity of dopamine receptors based on the observation that some headaches showed higher PRL after taking dopaminergic agents [8]. Reduced responsiveness of pituitary lactotroph cells to the action of dopaminergic agents has also been postulated [9]. Other authors suggested a serotoninergic hyperfunction rather than dopaminergic dysfunction.…”
Section: Discussionmentioning
confidence: 99%